Alternatywne ujęcie pomiaru ryzyka dla szeregów finansowych - Stachura, Michał (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper treats of the risk measurement problem and proposes an alternative view for this question. Firstly, one may use such statistics as variational averages, entropy and approximate entropy instead of variance to express and measure risk associated with financial series. Secondly, a dynamic approach is suggested rather than synthetic, which enables a researcher to detect changes of risk level in time. Additionally, this approach broadens risk measurement interpretation since not only values of measure but also inconstancy and volatility of the values' series may indicate a high level of risk. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 388-396